(untitled) (Orfeu, 2017)
Musical creation, which 70 years ago was practiced only by professional musicians, is today accessible to amateurs and children. It can be their first musical experience, and the basis of an education. Study of compositional strategies shows that at the heart of the creative process is a “musical idea”. What is a “musical idea”? It is an interesting sound which attracts the attention of the musician and makes him want to extend it. To extend the discovery, the composer repeats it with variations. The musical idea, which a century ago was usually a theme or motif, is today more commonly a particular sonority. Repeating a distinctive sound and varying it, however, is typical of the sound-exploration behavior of early childhood, known as “circular reaction”. Thus, from childhood, it is possible to encourage exploratory behavior, which becomes invention once it is intentional. This behavior can be enriched by the dimension of symbols and afterward by a taste for creating. The child goes through the different forms of game-playing, as analyzed by Piaget: the sensorimotor game, the symbolic game, and the rule-based game. The role of the educator is then to stimulate and guide this spontaneous development. Certain equipment can help. After the age of about 9 or 10, the computer is a suitable tool for composition.